ANALYSIS OF SUCCESS FACTORS FOR TRANS METRO BANDUNG BUS STOPS - Rohmawati, Tatik; Hidayat, Fadlan Karunia (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The aim of the research is to determine the success factors of the Trans Metro Bandung bus stop in terms of physical facilities, capital and human resources. The theory used by Sedarmayanti is that the effectiveness of a program can be seen from inputs including physical facilities, capital and human resources. The research method is a descriptive method with a qualitative approach. Data collection techniques through observation, data studies and interviews. Informants included Bandung City Transportation Department officials and people using Trans Metro Bandung buses using purposive techniques. The results of the research show that the factors for the success of the Bandung Trans Metro Bus Stop in terms of physical facilities, capital and human resources are not yet effective because the infrastructure is still lacking, costs are still limited and human resources are still small. Of course this research has a big impact on the public. TMB bus users